Faktor-faktor yang mempengaruhi tingkahlaku selamat dalam kalangan pekerja industri pembinaan di Malaysia - Adi Budiman, Abdul Razak (2019)
This study aims to examine the direct relationship between organizational support, employee competency, safety commitment, and safe behavior among construction industry workers in Malaysia. The construction industry was selected for the purpose of this study as employees in this sector were exposed to hazards and high risks at work. The dependent variable of this study is a safe behavior among employees. There are three independent variables which are organizational support, employee competency, and safety commitment. The total population for this study are 200 persons. Hence, a total of 127 questionnaires have been distributed and only 115 questionnaires were returned and can be used for further analysis. Multiple regression analysis has been used to determine the significant factor contribute to safe behavior at selected construction site.